Enhanced Online Payment Security using Steganography, Quantum and Visual Cryptography - Arele, Anshu; Sejwar, Vikas (International Journal of Computer Sciences and Engineering, 2025)
Visual Cryptography is Secret Sharing Scheme where it is an encryption methodology to hide the data under image in a fashion that it can only be decrypted by the combination of two shares. Quantum mechanics is the bsis of Quantum Cryptography Techniques. Use of Quantum key is the basis as Quantum mechanics concept has been utilized to have encrypted key in place between users and not used for data transmission. Steganography involves techniques of hiding information under other information so that extraction of data become difficult .In the existing work, it used these three techniques to improve the transaction security. But this is not enough to secure so to overcome this problem we apply image sequence and send OTP in the email id which makes them more secure to achieve more security.